Bone and joint lesions - Mendes, Rinaldo Poncio [UNESP] (Taylor & Francis, 2018)
Bone and joint involvement in paracoccidioidomycosis was first reported in 1911. Bone lesions occur at all age groups but younger patients are more frequently affected. The distribution of patients with bone lesions according to sex seems to be the same observed in cases with other involved organs. Isolated lesions are characterized by granulomatous reaction with great numbers of epithelioid and giant cells, which enclose the fungus. Disseminated lesions begin with necrosis and intense osteolysis, easily visible on radiological examination. The bone lesions are more frequent in the superior limbs and chest: clavicles, humeri, acromions, ribs, and radii. However, any bone may be affected. The etiological diagnosis of bone and joint involvement in paracoccidioidomycosis can be done by a surgical or percutaneous needle biopsy or by fine needly aspiration. Bone involvement by tuberculosis, an endemic disease in Latin America, is one of the most important differential diagnosis.